Morphological Characteristics and Nest Structure of Stingless Bee (Heterotrigona itama) from Different Meliponiculture Practices - Kadarsah , Anang; Putra, Aminuddin Prahatama; Nurliani, Anni; Suhartono, Eko; Ibrahim, Sayed (Biosaintifika: Journal of Biology & Biology Education, 2024)
Exploration of Heterotrigona itama biology characteristics besides being valuable for health and biodiversity also beneficial as well as an environmental bioindicator. This research aims to evaluate morphology characteristics and nest structure of stingless bee Heterotrigona itama from three different meliponiculture practices (MP1:meliponiculture in the back yard; MP2:meliponiculture in the rubber garden and MP3: meliponiculture in the side yard) in Banjar Regency, Indonesia. The parameters studied are morphology, nest design, colony structure, and environmental suitability. One-way ANOVA at a 95% confidence level was used to analyze differences between parameters. The results show Heterotrigona itama body size average from rubber gardens is bigger (7.11±0.60 mm) than the side yard (6.79±0.34 mm) and back yard (6.64±0.46 mm). The degree of difference is visible in the fore leg (α=0.00<0.05) and hind leg (α=0.004<0.05). The nest structure in MP3 was significantly different than MP1 and MP2, especially in terms of funnel length (p=0.007<0.05) and nest height from the ground  (p=0.000<0.05).  Environmental conditions MP3  (temperature 31.69±1.93 0C, humidity 60.70±11.2 % and water source) is more supportive for meliponiculture than MP2 (disturbed by household waste) and MP3 polluted by chicken farms. Meliponicultures practices based on various locations and environmental characteristics influence several parameters of Heterotrigona itama morphology and nest structure.